ASSOCIATION BETWEEN ALCOHOL CONSUMPTION AND ARTERIAL HYPERTENSION - Zajc, Jelena (Srpski medicinski časopis Lekarske komore, 2023)
Introduction/Aim: Arterial hypertension is a condition of chronically elevated levels of arterial blood pressure of 140/90 mmHg and higher, and is one of the leading causes of death, both worldwide and in Serbia. The aim of this study is to examine the association between the consumption of alcoholic beverages and arterial hypertension. Methodology: This cross-sectional study included 57 participants of both sexes (30 women and 27 men), over 18 years of age, from the wider area of the City of Pančevo, who were not on antihypertensive therapy. A survey was conducted to collect data on alcohol consumption, using the modified Food Frequency Questionnaire at a Glance of the National Institutes of Health, Bethesda, Maryland, USA. Measurement of arterial blood pressure was performed according to the recommended procedure, wherein the mean value was calculated, and the level of arterial blood pressure was categorized, in accordance with the classification of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH), from 2018. The data was processed in SPSS (Statistical Package for Social Sciences), the 2 test was applied, with the statistical significance threshold set at p < 0.05. The results are presented in textual and tabular form. Results: In the analyzed population, of the 43 participants who did not engage in risky alcohol consumption, 35 (81.4%) participants did not have hypertension, while 8 (18.6%) participants had hypertension. Among the 14 participants who engaged in risky alcohol consumption, 13 (92.9%) participants did not have hypertension, while one (7.1%) participant had hypertension. There was no statistically significant difference regarding the presence of hypertension with respect to the frequency of alcohol consumption (p > 0.05). Conclusion: There is no association between the consumption of alcoholic beverages and arterial hypertension.